2007
DOI: 10.1021/cm070078f
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Study of the Calcination Cycle from Gibbsite to Corundum

Abstract: A comprehensive picture of the gibbsite (Al(OH)3) to corundum (α-Al2O3) calcination process has been developed by multi-technique characterization of an integrated sample set. In 100 °C calcination stages, 27Al nuclear magnetic resonance (NMR), differential thermal analysis (DTA), X-ray diffraction (XRD), and nitrogen sorption surface area measurements were employed to elucidate the structure and chemistry of these calcinates. In addition, positron annihilation lifetime spectroscopy (PALS) has been used to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 34 publications
(69 reference statements)
8
41
0
Order By: Relevance
“…[49] In Fig. 5 we compare the theoretical spectra with the experimental data by O' Dell et al 19 (left panel, 14.1 T), and by Hill et al 18 (right panel, 9.4 T). We also compared with the 9.4 T spectrum by Pecharromán et al 55 (not shown) which agrees very well with the one by Hill et al.…”
Section: Fig 3 (Color On-line) Comparison Between the Experimentalmentioning
confidence: 86%
See 1 more Smart Citation
“…[49] In Fig. 5 we compare the theoretical spectra with the experimental data by O' Dell et al 19 (left panel, 14.1 T), and by Hill et al 18 (right panel, 9.4 T). We also compared with the 9.4 T spectrum by Pecharromán et al 55 (not shown) which agrees very well with the one by Hill et al.…”
Section: Fig 3 (Color On-line) Comparison Between the Experimentalmentioning
confidence: 86%
“…4 27 Al MAS NMR spectra from Ref. [18] for gibbsite and the theoretical spectrum obtained with the vdW-DF functional. Decomposition of the spectrum in individual components is also given.…”
Section: Gibbsite and Boehmite Phasesmentioning
confidence: 99%
“…In that case, dehydration of these hydrates would also contribute, although in small amount, to this LC [23]. The component at 297.3 ºC, representing a 3.0 %, should be assigned to gibbsite dehydroxylation [24,21]. As it was described for ungrounded samples [24], a further gradual weight loss could be completed by 700 ºC overlapping with other processes.…”
Section: Resultsmentioning
confidence: 95%
“…The 128 and 188 ºC LC account for almost a 3.5 % and can be easily assigned to gypsum and bassanite dehydration, which were identified by XRD [19,20]. The 254 ºC component, accounting for an 8.7 % of the weight loss, might have been contributed by evolved water from particle surfaces during the transition from gibbsite to boehmite since it was reported to take place in a range around 247 ºC [21,22]. According to Table 1, small amounts of magnesium carbonate hydrates may exist.…”
Section: Resultsmentioning
confidence: 99%
“…The results show large changes in structure at calcination temperatures between 200 and 300 • C. Large changes in structure are also thought to occur in the range 900 to 1000 • C. Weller 17) and Peri 18) report that water molecules dissociatively adsorb onto aluminum oxide; dissociative adsorption has also been reported for boehmite. 19) The phases from GB to corundum by calcination were reported by Hill et al 20) Table 1 shows the relationship between GB calcination temperature and the specific surface area, the surface pH and the concentration of surface hydroxyl groups. In these results, the specific surface area increased greatly at a calcination temperature of 300 • C, reached a maximum at a calcination temperature of 400 • C, and then decreased as the calcination temperature rose.…”
Section: Methodsmentioning
confidence: 98%